2011
DOI: 10.1007/s11655-011-0937-2
|View full text |Cite
|
Sign up to set email alerts
|

Red ginseng for type 2 diabetes mellitus: A systematic review of randomized controlled trials

Abstract: The evidence for the effectiveness of RG in controlling glucose in type 2 DM is not convincing. Few included studies with various treatment regimens prohibit definitive conclusions. More rigorous studies are needed to clarify the effects of RG on this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Two recent systematic reviews assessing the efficacy and safety of ginseng reported promising, but inconclusive evidence for its application in moderating glucose metabolism [12], [13]. However, another earlier systematic review and meta-analysis failed to show a FBG-lowering effect of ginseng supplementation [14]. One reason for these inconsistencies may relate to differences in their eligibility criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent systematic reviews assessing the efficacy and safety of ginseng reported promising, but inconclusive evidence for its application in moderating glucose metabolism [12], [13]. However, another earlier systematic review and meta-analysis failed to show a FBG-lowering effect of ginseng supplementation [14]. One reason for these inconsistencies may relate to differences in their eligibility criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, systematic reviews of such trials investigating the effect of ginseng on glycemic and metabolic parameters were largely inconclusive, concluding a lack of convincing evidence for benefit [10], [11] or reporting promising results for improving glucose metabolism [12], [13]. A previously conducted systematic review and meta-analysis on a single variety of ginseng, Korean red ginseng, did not show favorable outcomes in the management of T2DM, but was limited to 4 trials with incompatible study designs, as both acute and long-term effects of Korean red ginseng were investigated [14]. Therefore, our objective was to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) assessing for the first time, the glycemic effects of all species of ginseng (the genus Panax ) in people with and without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Collectively these studies failed to show effects on glucose metabolism that were different from placebo. We therefore concluded that "the evidence... is largely negative" [17].…”
Section: Clinical Efficacy Of Panax Ginsengmentioning
confidence: 93%
“…To a large extent, this is due to the frequently poor quality of the primary studies. All the above-mentioned systematic reviews note that most of the included clinical trials are methodologically fl awed [9][10][11][12][13][14][15][16][17]28]. It follows that, in order to render the fi ndings more conclusive, more rigorous trials are required.…”
Section: Implications For Future Clinical Re-searchmentioning
confidence: 99%
“…The major pathophysiologic mechanism of glucose intolerance is glucocorticoid-induced insulin resistance resulting in an increment in hepatic gluconeogenesis [7]. Among the pharmacologic activities of KRG, the hypoglycemic effect has been most extensively studied [8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%